Determinants of West Java MSMEs Readiness to Support Indonesia's Journey Towards a Global Halal Hub - Nugraha, Arinaldi; Yunanda, Rochania Ayu; Heryahya, Andang (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the determinants of West Java MSMEs' readiness for the intention to contribute to the Global Halal Hub (GHH) using the Theory of Planned Behavior (TPB). Methodology: A systematic random sampling survey was employed to gather data, and an online questionnaire was disseminated to MSMEs in West Java that had obtained halal certification. SmartPLS 3.2.9 was utilized to conduct an analysis of the data gathered from 150 respondents by Structural Equation Modeling (SEM). Results: The research findings indicate that all TPB variables (attitude, subjective norm, and perceived behavioral control) and government support were found to have a positive and statistically significant impact on the readiness of West Java MSMEs. However, religiosity did not have a positive and significant effect on the readiness of West Java MSMEs. Conclusion: Overall, the readiness variable was found to have a dominant, positive, and significant influence on the intensity of West Java MSMEs' intention to contribute to the GHH. Limitation: This study is limited to certain MSMEs, affecting generalizability, and relies on potentially biased survey and interview data. External factors like regulations and supply chains were not deeply explored. Future research with broader samples and methods is needed to better understand MSMEs' readiness for the Global Halal Hub. Contribution: It is expected that this research can serve as a foundation for the development of programs that support the readiness of MSMEs in meeting halal standards and competing in the global market.